2003
DOI: 10.1177/153537020322800403
|View full text |Cite
|
Sign up to set email alerts
|

Verotoxin-Producing Escherichia coli in Spain: Prevalence, Serotypes, and Virulence Genes of O157:H7 and Non-O157 VTEC in Ruminants, Raw Beef Products, and Humans

Abstract: In Spain, as in many other countries, verotoxin-producing Escherichia coli (VTEC) strains have been frequently isolated from cattle, sheep, and foods. VTEC strains have caused seven outbreaks in Spain (six caused by E. coli O157:H7 and one by E. coli O111:H- [nonmotile]) in recent years. An analysis of the serotypes indicated serological diversity. Among the strains isolated from humans, serotypes O26:H11, O111:H-, and O157:H7 were found to be more prevalent. The most frequently detected serotypes in cattle we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
3
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 39 publications
11
82
3
7
Order By: Relevance
“…Haemorrhagic colitis and haemolytic-uraemic syndromes had a close association with non-O157 STEC serogroups such as O26, O91 and O78, causing a threat to human health (Seto et al, 2007). The serogroups of STEC identified in the present study were shown to be O36, O60, O77, O78, O158 and O78&O92, among which O77 had been detected in STEC of cattle and sheep (Blanco et al, 2003), and STEC O78 had been found in humans, sheep, pigs and birds, and it was also the predominant serogroup of APEC (Fratamico et al, 2004;Shaheen et al, 2004). O158 has also been found in STEC strains isolated from cattle and sheep (Fratamico et al, 2004;Wenz et al, 2006).…”
Section: Discussionmentioning
confidence: 72%
“…Haemorrhagic colitis and haemolytic-uraemic syndromes had a close association with non-O157 STEC serogroups such as O26, O91 and O78, causing a threat to human health (Seto et al, 2007). The serogroups of STEC identified in the present study were shown to be O36, O60, O77, O78, O158 and O78&O92, among which O77 had been detected in STEC of cattle and sheep (Blanco et al, 2003), and STEC O78 had been found in humans, sheep, pigs and birds, and it was also the predominant serogroup of APEC (Fratamico et al, 2004;Shaheen et al, 2004). O158 has also been found in STEC strains isolated from cattle and sheep (Fratamico et al, 2004;Wenz et al, 2006).…”
Section: Discussionmentioning
confidence: 72%
“…E. coli O157:H7 has been widely known to be directly linked with foodborne infections, however, outbreaks due to non-O157 E. coli have increased recently [4]. Other serogroups including E. coli O26, O91, O103, O111, O118, O113and O145 have been reported as STEC [5][6][7]. Many STEC harbor shiga toxin 1 and shiga toxin 2 genes (stx1and stx2), such genes are responsible for the damage of endothelial and tubular cells resulting in acute renal failure [8].…”
Section: Introductionmentioning
confidence: 99%
“…Shedding of VTEC by cattle is generally intermittent, with herd members remaining negative for months, with only a proportion sporadically becoming positive for a few weeks at a time (30,31). Carriage rates are higher in calves than in adult cattle, and while detected all year-round, carriage rates are subject to seasonal effects, with higher rates reported in spring and summer.…”
Section: Bovine Carriage Of Vtecmentioning
confidence: 98%